Pembuatan Nano Partikel Kalsium (Ca) dari Limbah Tulang Ikan Patin (Pangasius sp) Menggunakan Metode Ultrasound- Asissted Solvent Extraction - Nuramaniyah Taufiq; Risky Nurul Fadlila RN (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2021)
Management of fish bones asa a source of calcium must be converted into a smaller form so that it is easily absorbed by the body into nanocalsium. In this case, fish bones are seen as giving a lot of advantages because fish are easier to get. The purpose of this study was to utilize catfish(Pangasius Sp) bones as the main ingredient for the manufacture of nanocalcium and extract fish bone lead using the Ultrasonic-Assisted Solvent Extraction method. This research method is characterization . of cat fish bone waste making nano particles using the Ultrasonic-Assisted solvent method, and characterized SEM-EDX. The result showed that the characteristic of catfish bone powder waste were 10,35 % water content, 44,29 % ash content, 1,849 fiber content, 11,47 % fat content, 0,27% protein content, and carbohydrates 33,62%, and SEM result for the morphological size 5.000x magnification, the particle diameter 3111,08 nm and EDX was 6 % purity of calcium (Ca).